Herramienta para el diseño de elementos estructurales de madera nacional mediante los métodos ASD y LRFD - Rojas-Barrantes, César Enrique (Instituto Tecnológico de Costa Rica, 2010)
As a result of this project, we created a tool oriented to this material to this material so important to the sector of construction called timber. This application facilitates the design progress of raw material under LRFD and ASD methods. The application was made in excel 2007 that generates summary sheets that work in turn reports to calculate and distinct for the use of professionals involved with this type of design. During the construction of the tool took into consideration the criteria of professionals involved with the design of wood. In addition to a series of information related to this issue that one way or another were the basis for reaching an appropriate application to reduce delivery times of projects. The completion of the project leads us to recognize the importance of such a tool, to facilitate decision marking involved in this project developed which involve important raw material in the field of construction. All this for the sole purpose of optimizing as much as possible surrounding the timber is sold nationwide.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2010.
Keywords: Aserradero; Compresión; Columnas; Cerchas; Carga